STABILITY ANALYSIS OF GROUND BASE 250 MLD BALANCING TANK (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Balancing tank is a structure which is utilized to store water & supply it to villages for drinking purpose, where there is scarcity of water during summer season. Here I have considered a balancing tank which is a ground base tank used to store water of capacity 260 ML per day for the purpose of supplying water to six villages. In this paper I have studied the causes of failure of balancing tank by comparative analysis of stability against overturning and sliding with & without considering IS 456-2000 code clause of stability. It is also check for safe bearing pressure of soil. As the capacity of tank is 250 MLD the wall of water tank is analyzed as ground base water retaining structure rather than considering water tank cases which have different methods of analysis.